2013
DOI: 10.1038/ejcn.2013.127
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water contributes to excessive iodine intake among children in Hebei, China

Abstract: Iodine in drinking water was identified to be the key contributor to this excessive iodine in children indicating that in these areas, intervention should focus on providing alternative drinking water supplies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
4
8
0
1
Order By: Relevance
“…This finding is consistent with other studies conducted in the HIAs in China [19,20]. These studies suggested that the population's iodine excess in the HIA was mainly caused by drinking water with high iodine content.…”
Section: Discussionsupporting
confidence: 95%
“…This finding is consistent with other studies conducted in the HIAs in China [19,20]. These studies suggested that the population's iodine excess in the HIA was mainly caused by drinking water with high iodine content.…”
Section: Discussionsupporting
confidence: 95%
“…Before the mandatory USI this percentage was 24%-25% [23,24]. It has been shown that local or regional geographical variation of I in DW exists and can be important for the I intake of the population, especially in areas where DW is of groundwater origin, as in Denmark [3,21,25] or China [26,27]. As part of our previous study, the DW contribution to dietary I intake in Denmark was estimated to vary in different parts of the country from 0% to above 100% (adults) or 50% (adolescents) of the RNI [3].…”
Section: Iodinementioning
confidence: 98%
“…In some areas of China, drinking water with high levels of iodine has been reported and identified as the key contributor to iodine excess [19,20]. Such iodine-rich drinking water has also been found in Somalia [21], Saharawi [22] and Europe [23].…”
Section: Iodine: An Abundant and Easily Accessible Environmental Rmentioning
confidence: 99%